Trends in Medicare Reimbursement for the Top 20 Surgical Procedures in Craniofacial Trauma. Issue 1 (1st January 2023) - Kandi, Lyndsay A.; Jarvis, Tyler L.; Shrout, Max; Thornburg, Danielle A.; Howard, Michael A.; Ellis, Marco; Teven, Chad M.
Abstract : Background: Research regarding financial trends in craniofacial trauma surgery is limited. Understanding these trends is important to the evolvement of suitable reimbursement models in craniofacial plastic surgery. The purpose of this study was to evaluate the trends in Medicare reimbursement rates for the top 20 most utilized surgical procedures for facial trauma. Methods: The 20 most commonly utilized Current Procedural Terminology (CPT) codes for facial trauma repairs in 2018 were queried from The National Summary Data File from the Centers for Medicare & Medicaid Services (CMS). Reimbursement data for each procedure was then extracted from The Physician Fee Schedule Lookup Tool. Changes to the United States consumer price index (CPI) were used to adjust all gathered data for inflation to 2021 US dollars (USD). The average annual and the total percent change in reimbursement were calculated for the included procedures based on the adjusted trends from the years 2000 to 2021. Results: From 2000 to 2021, the average reimbursement for all procedures decreased by 16.6% after adjusting for inflation. Closed treatment of temporomandibular joint dislocation and closed treatment of nasal bone fractures without manipulation demonstrated the greatest decrease in mean adjusted reimbursement at −48.7% and −48.3%, respectively, while closed treatment of nasal bone fractures without stabilization demonstrated the smallest mean decrease at −1.4% during the study period. Open treatment of nasal septal fractures with or without stabilization demonstrated the greatest increase in mean adjusted reimbursement at 18.9%, while closed treatment of nasal septal fractures with or without stabilization demonstrated the smallest increase at 1.2%. The average reimbursement for all closed procedures in the top 20 decreased by 19.3%, while that for all open procedures decreased by 15.5%. The adjusted reimbursement rate for all top 20 procedures decreased by an average of 0.8% each year. Conclusions: To the best of our knowledge, this is the first study to comprehensively evaluate trends in Medicare reimbursement for facial trauma surgical repairs. Adjusting for inflation, Medicare reimbursement for the top 20 most commonly utilized procedures has largely decreased from 2000 to 2021. Consideration of these trends by surgeons, hospital systems, and policymakers will be important to assure continued access to meaningful surgical facial trauma care in the United States.